Dibutyltin Compounds Effects on PPARγ/RXRα Activity, Adipogenesis, and Inflammation in Mammalians Cells - Milton, Flora A.; Lacerda, Mariella G.; Sinoti, Simone B. P.; Mesquita, Pedro G.; Prakasan, Dileesh; Coelho, Michella S.; de Lima, Caroline L.; Martini, Alexandre G.; Pazzine, Gabriela T.; Borin, Maria de F.; Amato, Angelica A.; Neves, Francisco de A. R. (Frontiers in Pharmacology, 2017)
Organotins are a group of chemical compounds that have a tin atom covalently bound to one or more organic groups. The best-studied organotin is tributyltin chloride, which is an environmental pollutant and an endocrine disruptor. Tributyltin chloride has been shown to bind to PPARγ/RXRα and induces adipogenesis in different mammalian cells. However, there are few studies with other organotin compounds, such as dibutyltins. The aim of this study was to investigate the effect of dibutyltins diacetate, dichloride, dilaurate, and maleate on the transcriptional activity of the nuclear PPARγ and RXRα receptors, and on adipogenesis and inflammation. Analogous to tributyltin chloride, in reporter gene assay using HeLa cells, we observed that dibutyltins diacetate, dichloride, dilaurate, and maleate are partial agonists of PPARγ. Unlike tributyltin chloride, which is a full agonist of RXRα, dibutyltins dichloride and dilaurate are partial RXRα agonists. Additionally, the introduction of the C285S mutation, which disrupts tributyltin chloride binding to PPARγ, abrogated the dibutyltin agonistic activity. In 3T3-L1 preadipocytes, all dibutyltin induced adipogenesis, although the effect was less pronounced than that of rosiglitazone and tributyltin chloride. This adipogenic effect was confirmed by the expression of adipogenic markers Fabp4, Adipoq, and Glut4. Exposure of 3T3-L1 cells with dibutyltin in the presence of T0070907, a specific PPARγ antagonist, reduced fat accumulation, suggesting that adipogenic effect occurs through PPARγ. Furthermore, dibutyltins dichloride, dilaurate, and maleate inhibited the expression of proinflammatory genes in 3T3-L1 cells, such as Vcam1, Dcn, Fn1, S100a8, and Lgals9. Additionally, in RAW 264.7 macrophages, tributyltin chloride and dibutyltin dilaurate reduced LPS-stimulated TNFα expression. Our findings indicate that dibutyltins diacetate, dichloride, dilaurate, and maleate are PPARγ partial agonists and that dibutyltins dichloride and dilaurate are also partial RXRα agonists. Furthermore, dibutyltins induce adipogenesis in a PPARγ-dependent manner and repress inflammatory genes in 3T3-L1 and RAW 264.7 cells. Although dibutyltins display some partial PPARγ/RXRα agonistic effects, the translation of cell-based results assays into in vivo effects on inflammation and insulin resistance is not entirely known. Nevertheless, further studies are necessary to address their effects in different periods of life and to elucidate the actions of organostanic compounds in whole-body context.